CT Angiography and Perfusion CT in Cerebral Vasospasm after Subarachnoid Hemorrhage - Binaghi, S.; Colleoni, M.L.; Maeder, P.; Uské, A.; Regli, L.; Dehdashti, A. R.; Schnyder, P.; Meuli, R. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: We investigated the association of multisection CT angiography (MSCTA) and perfusion CT (PCT) for the characterization of vasospasm secondary to aneurysmal subarachnoid hemorrhage.Materials and METHODS: Among 27 patients with symptomatic cerebrovascular vasospasm investigated by digital subtraction angiography (DSA), 18 underwent both cerebral PCT and MSCTA. For the remaining 9, only PCT or MSCTA could be performed. MSCTA was compared with DSA for the detection and characterization of vasospasm on 286 intracranial arterial segments. PCT maps were visually reviewed for mean transit time, relative cerebral blood flow, and relative cerebral blood volume abnormalities and were qualitatively compared with the corresponding regional vasospasm detected by DSA.RESULTS: Vasospasm was grouped into 2 categories: mild-moderate and severe. The depiction of vasospasm by MSCTA showed the best sensitivity, specificity, and accuracy at the level of the A2 and M2 arterial segments (100% for each), in contrast to the carotid siphon (45%, 100%, and 85% respectively). The characterization of vasospasm severity by MSCTA showed a sensitivity, specificity, and accuracy of 86.8%, 96.8%, and 95.2%, respectively, for mild-moderate vasospasm, and 76.5%, 99.5%, and 97.5%, respectively, for severe vasospasm. The PCT abnormalities were related to severe vasospasm in 9 patients and to mild-to-moderate vasospasm in 2. The sensitivity, specificity, and accuracy of PCT in detecting vasospasm were 90%, 100%, and 92.3%, respectively, for severe vasospasm, and 20%, 100%, and 38.5%, respectively, for mild-moderate vasospasm.CONCLUSION: MSCTA/PCT can assess the location and severity of cerebrovascular vasospasm and its related perfusion abnormalities. It can identify severe vasospasm with risk of delayed ischemia and can thus guide the invasive treatment.